Cuban Laurel Thrips, Gynaikothrips ficorum (Marchal) (Insecta: Thysanoptera: Phlaeothripidae) - Harold A. Denmark; Thomas R. Fasulo; Joseph E. Funderburk (EDIS)
Watson (1923) recorded the Cuban laurel thrips in Florida as Gynaikothrips uzeli (Zimmerman 1900). Since Priesner (1939) found that G. uzeli and G. ficorum (Marchal 1908) are distinct species, most specialists accept ficorum as the name of the Cuban laurel thrips. Specimens supposedly collected in Florida in 1887 are in the U.S. National Museum. G. ficorum appears in the Entomological Society of America's common name list as the Cuban laurel thrips, and is the name used here. This document is EENY-324 (IN599) (originally published as DPI Entomology Circular 59), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: August 2004. Revised: December 2005.